Executive Committee Minutes 2005-09-22 - Academic Senate:::::::::
Periodic Review of Administrators, Excellence in Teaching Award policy, Program Review Policy, Computer and Network Usage policy, Associated Students Resolution for Student Suffrage on Senate committees, Personal Confidential Information policy, Course Outline Policy